The Narrative Structure of Amy Tan’s ‘The Bonesetter’s Daughter’: Myth as a Critical Element - E. M. Karavaeva (Vestnik MGIMO-Universiteta)
The article explores Amy Tan's use of ghosts and spirituality in her novel 'The Bonesetter's Daughter'. The author studies how the belief in ghosts functions in the novel as an alternative perspective through which to understand life, social relations, and the cosmos. The spirit of Gu Liu Xin, the Chinese grandmother, plays a critical role in developing the psychological integrity of Ruth Luyi Young, the American-born Chinese granddaughter. It also helps guide Lu Ling, Liu Xin's daughter and Ruth's mother, out of the hazardous situation in China and sustains Lu Ling in times of alienation and hardship in America. The article concludes that spirituality is essential for a subjugated woman character to achieve her personal and political freedom as well as her physical and spiritual wholeness.